PERSPECTIVE OF CADETS TOWARDS MARITIME ENGLISH AT POLYTECHNICS OF MAKASSAR MERCHANT MARINE - Sunarlia Sunarlia Limbong (Universitas Islam Negeri Alauddin Makassar, 2021)
Foreign language instruction and learning are required component of all maritime institutions' curricula particularly English for marine communication. Because English has historically served as a maritime language across the globe. The purpose of this research is to ascertain seafarer cadets' perceptions on English language instruction in the deck and engine departments, as well as the critical nature of integrating technology into English instruction to assist their area of study. Respondents are the third semester cadets enrolled in the academic year 2019/2020 at the Deck Department. This study used quantitative descriptive. The survey is used to collect data on which abilities are most necessary to support their studies and future careers. The result of study showed that cadets’ attitudes about the usage of technology that would successfully assist them in accomplishing this objective Makassar Merchant Marine Polytechnic, being one of the maritime schools in Indonesia, develops seafarer candidates with distinct requirements and objectives that must be met with a precise and effective manner. A simulator and language laboratory are two types of language learning technologies that may aid in the teaching and learning of English, particularly for specialized reasons. And the majority of respondents think that using technology would assist them in learning English more effectively, it is critical for English instructors to include technology into the creation of English curricula for maritime cadets.